2021
DOI: 10.1002/hep.31417
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomics, Metabolomics, Predicted Metagenomics, and Hepatic Steatosis in a Population‐Based Study of 1,355 Adults

Abstract: Background and Aims Previous small studies have appraised the gut microbiome (GM) in steatosis, but large‐scale studies are lacking. We studied the association of the GM diversity and composition, plasma metabolites, predicted functional metagenomics, and steatosis. Approach and Results This is a cross‐sectional analysis of the prospective population‐based Rotterdam Study. We used 16S ribosomal RNA gene sequencing and determined taxonomy using the SILVA reference database. Alpha diversity and beta diversity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 50 publications
0
40
0
1
Order By: Relevance
“…Clinical and animal studies have shown that dysbiosis of the gut microbiota represents an independent risk factor for NHS [ 1 , 5 ]. Indeed, since alterations the gut microbiota can contribute to insulin resistance, chronic inflammation, and disorders of glucose, lipid, and amino acid metabolism, the gut microbiota is considered an important target for NHS treatment [ 1 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical and animal studies have shown that dysbiosis of the gut microbiota represents an independent risk factor for NHS [ 1 , 5 ]. Indeed, since alterations the gut microbiota can contribute to insulin resistance, chronic inflammation, and disorders of glucose, lipid, and amino acid metabolism, the gut microbiota is considered an important target for NHS treatment [ 1 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic hepatic steatosis (NHS) is the most common liver disease in the world and is associated with increased the risk of cardiovascular disease, type-2 diabetes, and liver-related complications such as hepatocellular carcinoma [ 1 3 ]. The occurrence and progression of NHS result from a combination of multiple genetic and environmental factors [ 1 ]. However, the factors that are currently known represent only a small fraction of those involved in disease onset and progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive association of diet quality with the Eubacterium eligens group agrees with its higher abundance among those with a vegetarian diet in Thailand (40) . Although we are not aware of any connections with diet for Ruminococcus gnavus, it is known that this organism is involved in non-alcoholic fatty liver disease (41) . Also diets rich in animal products have been associated with Collinsella and Ruminococcus gnavus, two pro-inflammatory genera (42) .…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Second, the gene‐targeted amplicons and metagenomics big data could support the integration of novel microbiome signatures. On the one hand, a large‐scale study on thousands of participants has revealed the association of gut bacterial diversity and composition, plasma metabolites, predicted functional pathways, and steatosis by 16S ribosomal RNA gene sequencing 29 . On the other hand, by shotgun sequencing, an integration study on the basis of fecal metagenomes, hepatic transcriptomes, and plasma and urine metabolomes has revealed hepatic steatosis‐associated molecular networks underlying the interaction between gut microbiome and the host phenome 30 .…”
Section: Methods and Resultsmentioning
confidence: 99%